1st to die - Patterson, James, 1947- (Patterson, James, 1947- Women's murder club., 2005)
Patterson debuts his new series introducing the Women's Murder Club. A demented killer stalks and murders newlyweds in San Francisco. Four women-a police detective, an assistant D.A., a reporter, and a medical examiner-join forces as they sidestep their bosses to track down a criminal whose twisted imagination stuns an entire city.